2011
DOI: 10.1001/archdermatol.2011.191
|View full text |Cite
|
Sign up to set email alerts
|

Response to Antimalarial Agents in Cutaneous Lupus Erythematosus

Abstract: Objective: To demonstrate response to antimalarial agents in patients with cutaneous lupus erythematosus (CLE) using activity scores from the Cutaneous Lupus Erythematosus Disease Area and Severity Index, a validated outcome measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 31 publications
4
89
0
4
Order By: Relevance
“…In addition to this, one can search for Anti-La [6] [8] [11], which shows positivity when above 10.0 U/mL, and the patient has a value lower than 7.0 U/mL, which can also be present in the disease and comes according to the literature, because Anti-La is found in only approximately 10% of lupus carriers [6] Treatment can be done by topical sunscreens, steroids and calcineurin inhibitors, while more severe conditions can be treated with hydroxychloroquine and systemic steroids [28] [29] [30] [31]. The patient was duly approached, being treated with hydroxychloroquine 400 mg/day and together with the use of sunscreen.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, one can search for Anti-La [6] [8] [11], which shows positivity when above 10.0 U/mL, and the patient has a value lower than 7.0 U/mL, which can also be present in the disease and comes according to the literature, because Anti-La is found in only approximately 10% of lupus carriers [6] Treatment can be done by topical sunscreens, steroids and calcineurin inhibitors, while more severe conditions can be treated with hydroxychloroquine and systemic steroids [28] [29] [30] [31]. The patient was duly approached, being treated with hydroxychloroquine 400 mg/day and together with the use of sunscreen.…”
Section: Discussionmentioning
confidence: 99%
“…Lupus profundus, however, did not improve. In 2011, Chang et al (19) reported improvement in 67% of their patients treated with a combination of HCQ/ MPC (n = 15) and in 33% of their cases treated with a combination of CQ/MPC (n = 6).…”
Section: Discussionmentioning
confidence: 99%
“…Quinacrine was started in the majority (86.1%, n=241) of the remaining 280 due to hydroxychloroquine refractoriness, consistent with studies on its efficacy for recalcitrant disease. 3 Following initiation, quinacrine was discontinued in 50.4% (n=141), hydroxychloroquine in 44.5% (n=237), and chloroquine in 62.2% (n=61). Patients on these medications are not mutually exclusive as most were on either hydroxychloroquine or chloroquine in combination with quinacrine.…”
Section: To the Editormentioning
confidence: 99%